Proceso de atención de enfermería en neonato de 28 semanas de gestación con displasia broncopulmonar. - Borja Ulloa, Fátima Esthefania (2023)
Bronchopulmonary dysplasia is a chronic disease that usually occurs in the majority of newborns born with low weight, who usually present this pathology. It is considered that it usually occurs when a neonate has a long hospital stay with continuous mechanical ventilation, which can make it difficult and present greater complications. That is why the present study was carried out on a 28-week male preterm neonate obtained by emergency cesarean section in the breech position who presented weak crying, acrocyanosis, respiratory tissue and marked intercostal indrawing. Based on this work, objectives are defined in which the main one is the application of nursing care processes in the aforementioned patient. In the development of this work, the theoretical foundations are made and at the same time the study of the patient is presented and at the same time the development of nursing activities is achieved for the benefit of the patient.